Intelligent In-House Monitoring for the Elderly - Vuong, Barry; Rzeszutek, Richard; Auciello, Paolo (CMBES Proceedings, 2007)
Heat emergencies such as heatstroke, high fever and occupational heat exposure are all serious medical conditions that require emergency response. These are of particular concern for the elderly or infirmed, who may be home alone and unable to summon help. We present a paper on an Intelligent In-House Monitoring system for the elderly, designed to collect both physiological and environmental data in order to determine if an individual is experiencing a heat emergency. This system was designed to non-intrusively and non-invasively measure pulse rate, perspiration and body temperature to determine whether or not a person is experiencing some sort of heat emergency. The monitoring system is comprised of a wearable monitor that transmits the information wirelessly to a base station that records both ambient air temperature and humidity. The base station combines the data from the monitor with the environmental data to determine if the wearer is experiencing a heat emergency. If it determines that a heat emergency is occurring then it will attempt to reach an emergency contact, as well as warn the wearer of the need to cool down.